The highly efficient gamma-neutron detector for control of fissionable radioactive materials - Ryzhikov, V.D.; Grinyov, B.V.; Onyshchenko, G.M.; Piven, L.A.; Naydenov, S.V.; Lysetska, O.K. (Functional Materials, 2014)
Comparative measurements and analysis of detection efficiency of fast and thermal neutrons from ²³⁹Pu-Be source by heavy oxide scintillators (Z≥50) confirmed high detection efficiency (∼ 40-50 %). The most probable mechanism determining the fast neutron detection efficiency is the reaction of inelastic scattering (n, n ′ γ ) as the main mechanism of interaction of neutrons with nuclei of oxide scintillators. The fast neutron detection efficiency was determined by the method of internal counting of gamma-quanta emerging in the scintillator under (n, n ′ γ ) reaction. It has been shown that the use of heavy oxide scintillators (which are also efficient gamma-detectors) in inspection systems can allow detection of fissionable radioactive materials.